2018
DOI: 10.1371/journal.pone.0195938
|View full text |Cite
|
Sign up to set email alerts
|

Associations of obesity with tracheal intubation success on first attempt and adverse events in the emergency department: An analysis of the multicenter prospective observational study in Japan

Abstract: Obesity is deemed to increase the risk of difficult tracheal intubation. However, there is a dearth of research that examines the relationship of obesity with intubation success and adverse events in the emergency department (ED). We analyzed the data from a prospective, observational, multicenter study—the Japanese Emergency Airway Network (JEAN) 2 study from 2012 through 2016. We included all adults (aged ≥18 years) who underwent tracheal intubation in the ED. Patients were categorized into three groups acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…This is an analysis of the data from a multicenter prospective observational study of consecutive ED patients who underwent emergency airway management— JEAN-2 registry from February 2012 through November 2016. The study design, setting, methods of data collection, and measured variables have been reported elsewhere 2125,27,28 . In brief, the JEAN-2 study is a consortium of 15 academic and community medical centers from different geographic regions across Japan.…”
Section: Methodsmentioning
confidence: 99%
“…This is an analysis of the data from a multicenter prospective observational study of consecutive ED patients who underwent emergency airway management— JEAN-2 registry from February 2012 through November 2016. The study design, setting, methods of data collection, and measured variables have been reported elsewhere 2125,27,28 . In brief, the JEAN-2 study is a consortium of 15 academic and community medical centers from different geographic regions across Japan.…”
Section: Methodsmentioning
confidence: 99%
“…One possible explanation for the result is that the proportion of obesity in males was higher than that in females. Obesity has been considered to be a risk factor for difficult laryngoscopy [17]. Another potential explanation might be the anatomical differences between males and females, such as soft tissues in the neck and fat distribution [18].…”
Section: Discussionmentioning
confidence: 99%
“…33,46,47 Excessive body mass and obstructive sleep apnea might complicate different forms of respiratory support and endotracheal intubation. 48,49 Prolonged endotracheal intubation time, which is more frequently present in patients with obesity, also increases the risk of infection of the medical staff. 50 These are of particular importance considering that we have shown a greater risk for IMV in patients with higher BMI in all comparisons.…”
Section: Obesity and Icu Admissionmentioning
confidence: 99%